Enhancing students’ reading comprehension through the Jigsaw method: Evidence from a private senior high school in Palu, Central Sulawesi: PENERAPAN METODE JIGSAW UNTUK MENINGKATKAN PEMAHAMAN MEMBACA SISWA KELAS X DI SMA LAB SCHOOL UNTAD PALU - Tiara Lulu Gifarini; Sriati Usman; Mashuri Mashuri; Konder Manurung (University of Muhammadiyah Malang, 2025)
The objective of this study was to analyze the effect of the Jigsaw method on improving reading comprehension among tenth-grade students in the context of English as a Foreign Language (EFL) instruction in high schools. The research method employed was a quasi-experimental design, which included pre-tests and post-tests. The study's participants were 52 students who were selected through simple random sampling from a population of 183 tenth-grade students Class XD, consisting of 26 students, served as the experimental group, while Class XC, with 26 students, served as the control group. The results show that the average pre-test score of the experimental group increased significantly from 44.27 to 86.38 after the intervention. In contrast, the average score of the control group showed a marginal increase from 64.23 to 76.69. The analysis results showed a significance value of 0.002 < 0.05, indicating a significant improvement in reading comprehension between the experimental and control groups when using the Jigsaw method. The findings of this study suggest that the Jigsaw method is effective in enhancing students' reading comprehension. This study provides important contributions for teachers and education practitioners in designing collaborative and participatory reading instruction.